Inulin reduces liver triacylglycerol by increasing lipid droplet lipolysis in fat-loaded mice. (January 2023) - Chen, Bingbing; Shi, Yumeng; Zhang, Kai; Chang, Yanzhong; Fu, Pengcheng; Liu, Pingsheng; Zhang, Shuyan
Graphical abstract: Highlights: Inulin supplementation could alleviate high-fat diet-induced hepatic steatosis, mediated through increasing ATGL on liver lipid droplets. The beneficial effects of inulin, such as increasing energy expenditure, alleviating adiposity, and improving glucose intolerance, could only be achieved in mice fed with high-fat diet for 1 month, not for 4 months. Gut microbiota in the short- and long-term fat-loaded mice was shown to be modulated in a different way, which may mediate the differential effects of inulin. Abstract: Increased consumption of high-fat low-fiber foods has been shown to contribute to the development of metabolic syndromes, such as fatty liver, obesity, diabetes, et al . Fermentable dietary fiber, such as inulin, is broadly used to mitigate host metabolic abnormalities. In this work, we studied systematically the effect of inulin on mice with metabolic disorders, induced by either short- or long-term high-fat feeding. As expected, inulin reduced the body weight of mice in both groups. However, it was found that inulin feeding could only increase energy expenditure, alleviate adiposity, and improve glucose intolerance in mice fed with high-fat diet (HFD) for 1 month but not for 4 months. Surprisingly, inulin supplementation could alleviate HFD-induced hepatic steatosis, mediated through increasing adipose triglyceride lipase (ATGL) on liver lipid droplets, in both groups. Gut microbiota in the short- and long-term fat-loaded mice were shown to be modulated differently, which may mediate the differential effects of inulin. These results may help in understanding the role and mechanism of fermentable fiber regulating host metabolism.